ImmunoChip Study Implicates Antigen Presentation to T Cells in Narcolepsy - Faraco, Juliette; Lin, Ling; Kornum, Birgitte Rahbek; Kenny, Eimear E.; Trynka, Gosia; Einen, Mali; Rico, Tom J.; Lichtner, Peter; Dauvilliers, Yves; Arnulf, Isabelle; Lecendreux, Michel; Javidi, Sirous; et al. (PLoS genetics, 2013)
Recent advances in the identification of susceptibility genes and environmental exposures provide broad support for a post-infectious autoimmune basis for narcolepsy/hypocretin (orexin) deficiency. We genotyped loci associated with other autoimmune and inflammatory diseases in 1,886 individuals with hypocretin-deficient narcolepsy and 10,421 controls, all of European ancestry, using a custom genotyping array (ImmunoChip). Three loci located outside the Human Leukocyte Antigen (HLA) region on chromosome 6 were significantly associated with disease risk. In addition to a strong signal in the T cell receptor alpha (TRA@), variants in two additional narcolepsy loci, Cathepsin H (CTSH) and Tumor necrosis factor (ligand) superfamily member 4 (TNFSF4, also called OX40L), attained genome-wide significance. These findings underline the importance of antigen presentation by HLA Class II to T cells in the pathophysiology of this autoimmune disease.